2007
DOI: 10.1177/0731684407081355
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Thermal and Residual Stresses of Parabolic Temperature Loading in a Thermoplastic Composite Disc

Abstract: The aim of this study was to investigate of the effect on thermal and residual stresses of parabolic temperature loading in a thermoplastic composite disc. It was reinforced by steel-fibers as unidirectional for radial direction. The finite element method (FEM) was used to estimate the thermal elastic, elasto-plastic, and also the residual stress distributions in the selected model of the composite disc. Consequently, the thermal stress analysis was carried out using ANSYS finite element software. The temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In a different study, the calculated stresses on a disk with different mechanical properties were analyzed. Similarly, it has been found that the tangential stress is maximum in the innermost part of the disk and minimum in the outermost region [23] . In addition, it is believed that the results obtained by numerical analysis, a computer program, and the results obtained in Tables 2 and 3 above are quite close to the results obtained by the Chebsey method, which generally indicates that the results are correct.…”
Section: Conclusion and Discussionmentioning
confidence: 70%
“…In a different study, the calculated stresses on a disk with different mechanical properties were analyzed. Similarly, it has been found that the tangential stress is maximum in the innermost part of the disk and minimum in the outermost region [23] . In addition, it is believed that the results obtained by numerical analysis, a computer program, and the results obtained in Tables 2 and 3 above are quite close to the results obtained by the Chebsey method, which generally indicates that the results are correct.…”
Section: Conclusion and Discussionmentioning
confidence: 70%
“…Tabulated properties belong to glass fibers and epoxy resin. Subsequently, using the equations ( 2) to ( 9) and ( 45) to (48), composite properties are found. Also, throughout this subsection, following geometric dimensions are used: h a = 0.04 m, a = 0.04 m, and b = 0.10 m. In order to have a convex thickness profile, geometric parameter is set as n = 20.6.…”
Section: Rotating Convex Disk Under Radial Temperature Gradientsmentioning
confidence: 99%
“…Sayer et al 46 have carried out analytical and experimental solutions to analyze thermoelastic stresses in a fiber reinforced thermoplastic composite disk. Elastic-plastic stresses of a pressurized composite disk, which constituents metal fibers and aluminum matrix, under thermal loads are studied by Topcu et al 47 The examination of Sen 48 focused on the influence of thermal and residual stresses on composite thermoplastic disks.…”
Section: Introductionmentioning
confidence: 99%
“…It was found these two solutions are in good agreement. Sen [9] investigated the effect on thermal and residual stresses of parabolic temperature loading in a thermoplastic composite disc. FEM was used to estimate the thermal elastic, elasto-plastic, and also the residual stress distributions in the selected model of the composite disc using ANSYS.…”
Section: Introductionmentioning
confidence: 99%